PENGARUH POTONGAN HARGA TERHADAP PENJUALAN BUKU KOMIK ANAK ELEX MEDIA PADA PT. GRAMEDIA ASRI MEDIA CABANG MALL RATU INDAH MAKASSAR - Ester Tamallo (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
This study aims to identify and analyze the significance of the effect of discounts on sales of comic books on children PT Elex Media Scholastic Media Asri Ratu Indah Mall Branch Makassar. The method of analysis used in this research is descriptive qualitative analysis, by analyzing qualitative data was obtained through interviews and simple regression analysis, was used to determine the effect of price cuts on the level of sales. The results showed Effect rebates based on the results of a simple regression analysis, indicates that there is a significant and direct effect (positive) on an increase in sales of comic kids Elex Media with significance level of 0.018 (much less than 0.05) at PT Gramedia Asri Media Ratu Indah Mall branch Makassar, indicating that the hypothesis can be accepted. The relationship between the discounted price on sale at comic child PT Elex Media Scholastic Media Asri Ratu Indah Mall Makassar branch based on the results of correlation analysis showed a very strong relationship or correlated. This is indicated by the coefficient of determination (R2) of 0.881 or 88.1%. More influenced by factors other than the price cuts to service and quality.